2020
DOI: 10.18844/cjes.v15i4.5056
|View full text |Cite
|
Sign up to set email alerts
|

A model test towards university students’ cheating behaviour in the context of the theory of planned behaviour

Abstract: This study aimed to identify the causal relationships amongst attitude, subjective norms, perceived behavioural control, moral obligation and intention towards cheating by the Theory of Planned Behaviour. The study sample (n = 1,220) consists of senior students at the faculties of Van Yuzuncu Yil University, Turkey. The data were collected with the scales; attitude, subjective norms, perceived behavioural control, moral obligation and intention towards cheating, which were developed by researchers of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…Intention was the strongest direct antecedent for academic dishonesty in this study, which is consistent with most behavioral research (e.g., Ajzen, 1991; Beck & Ajzen, 1991; Yang, 2012b). Such that study often only measured intention rather than actual behavior when studying behavioral factors with the TPB (e.g., Cronan et al, 2018; Harding et al, 2007; Koc & Memduhoglu, 2020; Stone et al, 2007; Uzun & Kilis, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Intention was the strongest direct antecedent for academic dishonesty in this study, which is consistent with most behavioral research (e.g., Ajzen, 1991; Beck & Ajzen, 1991; Yang, 2012b). Such that study often only measured intention rather than actual behavior when studying behavioral factors with the TPB (e.g., Cronan et al, 2018; Harding et al, 2007; Koc & Memduhoglu, 2020; Stone et al, 2007; Uzun & Kilis, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In general, cheating behaviour is certainly widespread and a variety of factors have been identified as contributing to its extent and prevalence. It is suggested that students tend to cheat in the hopes of a lifelong satisfactory income and comfort [4].…”
Section: Cheating Behaviorsmentioning
confidence: 99%
“…Cheating behaviour is a form of academic misconduct or academic fraud that has become a serious phenomenon among university students [1][2][3]. Cheating behavior also can be known as academic fraud [4] (Carpenter, et al 2006). In connection with this, cheating behaviour is a worldwide problem, and a topic for study by researchers from various parts of the globe.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, it’s found, by referring to the previous discussion on relevant issues, that the Theory of Planned Behavior (TPB) is mainly applied to the behavioral intention of word-of-mouth on tourists’ purchase of souvenirs ( Lee, 2020 ) and the model testing of college students’ cheating behavior ( Koc and Memduhoglu, 2020 ); and that the situational influence is widely used in investigating the strategies of household consumption behavior ( Kuhe and Bisu, 2019 ), integration of social application software into aesthetic education ( Chen et al, 2020 ), etc. ; and that attitude, subjective norms, and perceived behavioral control (PCB) are mainly used to study the behavioral intentions and habits of enterprise employees in energy saving ( Chen and Chen, 2019 ), and those of young Vietnamese consumers in purchasing foreign coffee ( Su and Kang, 2019 ).…”
Section: Introductionmentioning
confidence: 99%